Macroeconomics - "Mankiw , N. Gregory" (New York, 2000)
The number one textbook for intermediate macroeconomics courses since its first edition, this title is known for conveying the cutting edge in macroeconomics theory, research, and policy to the classroom, explaining complex concepts with exceptional clarity.
Keywords: Macroeconomic policy